Construct of anti-corruption character using exploratory factor analysis (EFA) - Salimah, Zahrotun; Istiyono, Edi; Febrianto, Agus Dwi; Widihastuti, Widihastuti (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
Corruption is a highly complex problem in the current global era. One of the government's innovations in the battle against corruption is anti-corruption education. Along with the implementation of anti-corruption education, tools are needed to measure the success of implementing anti-corruption education programs through anti-corruption instruments. This study uses a quantitative research method with the Exploratory Factor Analysis (EFA) data analysis technique to show the validity of the construction of anti-corruption character assessment tools. The anti-corruption values consist of nine values: courage, justice, caring, simplicity and independence, hard work, responsibility, honesty, and discipline. This study uses the SPSS application to process EFA construct validity data. The questionnaire has been tested on 72 junior high school students. The study's findings show that the character evaluation tool satisfies a number of EFA requirements: 1) The criteria for adequacy of the sample with a KMO-MSA value of > 0.5 (0.681) and sig. 0.000 on Bartlett's Test. 2) All items can be carried out by factor analysis because they have an anti-image correlation value > 0.5. 3) There are eight factors formed from the eigenvalues of factor 1 (6.080), factor 2 (2.066), factor 3 (1.636), factor 4 (1.510), factor 6 (1.360), factor 7 (1.257), and factor 8 (1.085).